1970
DOI: 10.7307/ptt.v25i1.1246
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Procedures to Estimate Critical Headways at Roundabouts

Abstract: The capacity analysis of roundabouts in Portugal is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 16 publications
2
29
0
2
Order By: Relevance
“…The results revealed important specificities of the methods with significant effects on the capacity estimates. The comparison of the estimates with values from several countries indicated significant differences among them and suggested the presence of relevant driving style differences; as a consequence, Vasconcelos et al [55] came to the conclusion that locally calibrated, country-specific, parameters should be preferred for capacity calculations.…”
Section: Portuguese Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The results revealed important specificities of the methods with significant effects on the capacity estimates. The comparison of the estimates with values from several countries indicated significant differences among them and suggested the presence of relevant driving style differences; as a consequence, Vasconcelos et al [55] came to the conclusion that locally calibrated, country-specific, parameters should be preferred for capacity calculations.…”
Section: Portuguese Studiesmentioning
confidence: 97%
“…In another study Vasconcelos et al [55] estimated critical headways and follow-up times basing on observations at six Portuguese roundabouts; gap-acceptance data were collected at each entry, for the left-and right-lanes independently. The Authors applied several estimation methods: Siegloch [51], Raff [47], Wu [38], maximum likelihood [19] and logit method [54].…”
Section: Portuguese Studiesmentioning
confidence: 99%
“…Previous research from several countries has clearly shown that a properly designed roundabout can significantly improve traffic efficiency and road safety [6,7,8,9].…”
Section: Figure 1 -Ultra-large Roundabout In Livornomentioning
confidence: 99%
“…Therefore, predicting the potential operating speed at a roundabout, during its design stage, is vital to ensure that the expected operating speed will meet the design expectations and the safety target for that roundabout. Furthermore, the capacity of a roundabout is highly correlated with critical time headways and follow-up times selected by drivers [5][6][7][8][9], which are related to the operating speed at the roundabout [2,[10][11][12][13][14]. Therefore, predicting the operating speed will also help in estimating the potential capacity of the roundabout being designed and ensure that the capacity meets the design requirements and the expected traffic volume.…”
Section: Introductionmentioning
confidence: 99%